Illness in Hartmann von Aue’s Der arme Heinrich - PLANINIĆ, Luka (Anafora, 2023)
The topic of illness is currently omnipresent and more relevant than ever and in this article, it will be approached from various perspectives on the example of Hartmann von Aue’s narrative tale Der arme Heinrich. Illness has up to now been researched in this narrative tale either as an interpretation of the divine judgment or as a test of faith. This research offers new insight into depictions of illness in the context of religious subject matter and questions of sin and guilt addressed in this narrative tale, thus clarifying their function within the medieval court society and knighthood. Based on this, a hermeneutic approach and that of literary studies have been chosen in this article in order to analyse and interpret the role of disease regarding the medieval depiction of the estates of the realm and the differences between them. In this manner, the article offers a new perspective concerning the research of medieval perception of death, faith and society.